Performance comparison of SAR distributions in phantom bio-medium due to TiO2 loaded metal diagonal and square horn antennas - Singh S.; Katare K.K.; Patre S.R.; Singh S.P. (My University, 2025)
This paper investigates TiO2 loaded metal diagonal and square horn antennas and specific absorption rate (SAR) distributions in a phantom bio-medium due to these antennas through simulation. Diagonal horn is a multimode horn antenna whereas in conventional square horn only TE10 mode propagates. Both diagonal and square horns, which are terminated in a phantom bio-medium are designed and simulated at 2.45 GHz using FEM based Ansoft's HFSS software. The SAR distributions in the bio-medium due to diagonal and square horns are compared at 2.45 GHz. © 2013 IEEE.